Coworker reactions to a partner with a physical disability - Randall, Marjorie L., author; Cropanzano, Russell, advisor; Thornton, George C., 1940-, committee member; Slater, Michael, committee member; Rickard, Kathryn Marie, committee member (Colorado State University. Libraries, 1998)
The purpose of this study was to examine the relative impact of a task partner's physical disability, performance, and interpersonal behavior on the other partner's evaluations of and willingness to collaborate with that individual on a subsequent task. Participants were 198 students paired with a female confederate in one of eight combinations of conditions: nondisabled/disabled (paraplegic), success/failure, pleasant/unpleasant. Each participant/confederate pair completed a set of tasks, after which participants were asked to evaluate their partner and indicate how much they wanted to work with her again on a subsequent task. In general, participants did not respond the same way to the interpersonal behavior of a disabled confederate as they did with a nondisabled partner. Four theoretical models (kindness, social desirability, response amplification, reversed responses) were tested; none of these was supported. Contrary to findings of previous research, predicted affective response to disability was not found; rather, the findings support the notion of disability having a cognitive effect and moderating other variables' impact on evaluations and work-related decisions. Implications and suggestions for future research are discussed.
Keywords: People with disabilities -- Employment; Discrimination against people with disabilities; Sociology of disability